Utilizing mixed-mineralogy ferroan magnesite tailings as the source of magnesium oxide in magnesium potassium phosphate cement. (20th January 2020) - Ismailov, Arnold; Merilaita, Niina; Solismaa, Soili; Karhu, Marjaana; Levänen, Erkki
Graphical abstract: Highlights: A talc mine tailing (MT) was used as a source for MgO in MKPC. The pre-calcined tailing consisted of 80% MgCO3, the rest being mostly silicates. Calcination of MT was carried out at 350 °C–1400 °C. Calcination at 1200 °C and above reduced the phosphate reactivity excessively. Recommended calcination range was found by 4-point bending and solubility testing. Abstract: A mixed-mineralogy talc mine tailing (MT) fraction consisting of 80% ferroan magnesite (MgCO3 ) was studied for utilization as the source of magnesium oxide (MgO) in magnesium potassium phosphate cement (MKPC). The effects of calcination temperature of this low-grade magnesite on the composition, BET surface area and phosphate reactivity of the resulting magnesia powder were studied. The 4-point flexural strength of resulting MKPC was measured for all calcined raw material fractions that produced a solid. Based on the strength measurement results, the optimal range for calcination resided between 700 °C and 1150 °C, which is drastically lower than commonly recommended for finer magnesia sources in MKPCs. Accelerated reactivity assessment showed that phosphate reactivity behavior could not be entirely predicted by BET surface area. The presence of impurity silicates and high iron content in all the constituent minerals was posed as the reason for densification and loss of reactivity at higher calcination temperatures.